2000
DOI: 10.1111/j.1151-2916.2000.tb01645.x
|View full text |Cite
|
Sign up to set email alerts
|

Necessary Conditions for the Formation of {111} Twins in Barium Titanate

Abstract: The experimental conditions for {111} twin formation in BaTiO3 were investigated. When BaTiO3 compacts without excess TiO2 were sintered either in an oxidizing atmosphere (air) or in a reducing atmosphere (95N2–5H2), no {111} twins formed within the BaTiO3 grains and no abnormal grain growth occurred. In contrast, many {111} twins were present within the abnormally grown grains in the excess‐TiO2‐containing BaTiO3 samples sintered in air, while no twins were observed in the excess‐TiO2‐containing samples sinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Nowadays, there is sufficient experimental evidence that the existence of {111} twins alone does not trigger exaggerated grain growth, as initially proposed by Eibl et al 37 This is also true for LBTY ceramics, where exaggerated grain growth was not observed despite the existence of {111} twins. According to Lee et al , 38 the presence of {111} twins enhances exaggerated grain growth only when the grain boundaries are faceted.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there is sufficient experimental evidence that the existence of {111} twins alone does not trigger exaggerated grain growth, as initially proposed by Eibl et al 37 This is also true for LBTY ceramics, where exaggerated grain growth was not observed despite the existence of {111} twins. According to Lee et al , 38 the presence of {111} twins enhances exaggerated grain growth only when the grain boundaries are faceted.…”
Section: Discussionmentioning
confidence: 99%
“…30 In our Sb-BST and Sb-BST + TiO 2 samples, which each contained (Ba,Sr)Ti 6 O 17 and exhibited exaggerated grain growth, we did not observe any of the characteristic, elongated grains reported to be {1 1 1} twins in BaTiO 3 , and also reported in BST prepared by other research groups. 30,[41][42][43] The reasons for this discrepancy are unclear.…”
Section: Discussionmentioning
confidence: 87%
“…5a), unlike BaTiO 3 sintered at low temperatures (≈1,250°C [20,21]), were observed only occasionally. Both parts (i.e., A and B) of the twin-grain appear in different contrast due to a slight deviation from the Bragg position registered by the gvectors [25], i.e., Δg ¼ g A À g B , due to obliquity.…”
Section: Batio 3 Dielectric Layermentioning
confidence: 89%
“…However, no ferroelectric domains were detected from the BaTiO 3 grains. Twinning along {111} is occasionally found [20][21][22]37], both single [20,21,37] and double twins [20,21,37], as indicated by unfilled arrows in Fig. 5a.…”
Section: General Microstructure-om and Semmentioning
confidence: 94%